Air‐Permeable Textile Bioelectronics for Wearable Energy Harvesting and Active Sensing. Issue 8 (29th January 2023) - Zhao, Xun; Chang, Austin; Li, Justin; Xu, Jing; Hollister, John; Che, Ziyuan; Wan, Xiao; Yin, Junyi; Wang, Shaolei; Lee, Shinyoung; Kavehpour, Pirouz; Chen, Jun
Abstract: Advances in wearable bioelectronics enable the possibility of transforming the currently reactive and disease‐centric healthcare system to one focused on disease prevention and health promotion. Converting biomechanical activities into electrical signals could be a unique way to develop wearable bioelectronics for personalized healthcare. In this work, an air‐permeable textile (APT) bioelectronics is developed. It is formed with a liquid metal electrode treated with Nickel (Ni‐EGaIn) encapsulated between two layers of electrospun Polycaprolactone textile. With a size of 4 cm by 4 cm, the APT bioelectronics produces an open‐circuit voltage of 12 V and a short‐circuit current of 0.12 mA, ultimately outputting a power density of 7.975 W m −2 . The APT bioelectronics demonstrates an ability to produce electrical output under varying degrees of deformation with stable performance over 6000 cycles. In addition, the APT bioelectronics holds a drying rate of 5.07% min −1 compared to conventional fabrics such as polyester with a drying rate of 3.93% min −1 . This keeps the ATP dry and cool for decent wearing comfort. With a collection of compelling features, the air‐permeable textile bioelectronics represents a promising approach for human body centered energy and sensing applications. Abstract : An air‐permeable textile bioelectronics formed with a liquid metal electrode is reported. It is treated with Nickel encapsulated between two layers of electrospun Polycaprolactone textiles. The textile demonstrates its capability in producing electrical output under varying degrees of deformation. In addition, it holds a high drying rate of 5.07% min −1, which keeps itself dry for comfort when worn.